Metastasis of the abdominal wall in a patient with diagnosis of pulmonary adenocarcinoma: An interesting finding - Mancera, Juliana; Vergara, Arturo; Cadena, Manuel E.; Lozada-Martinez, Ivan David; Guardo-Carmona, Daniela; Cabrera-Vargas, Luis Felipe; Ataullah, A.H.M. (Respiratory medicine case reports, 2022)
Tumors of the abdominal wall are rare, divided into benign and malignant lesions that are composed of primary tumors and by the parietal invasion of intra-abdominal tumors and metastatic parietal implants. In the case of metastases in the abdominal wall, the most frequent are metastases from neoplasms of colonic origin. The case described below is that of a 68-year-old patient with a history of stage IIA left lung adenocarcinoma who received partial response radiotherapy with an indication for chemotherapy, which she refused and lost follow-up.